2023
DOI: 10.1021/acs.chemmater.3c00591
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of the New Solid-Solution (V1–xCrx)2GaC (0 ≤ x ≤ 1), a Pauli Paramagnet Almost Matching the Stoner Criterion for x = 0.80

Abstract: MAX phases that exhibit long-range magnetic order in the bulk are still very hard to synthesize. Chromium and manganese are the cutoff elements when transitioning through the 3dmetals that still form stable full and doped MAX phases, respectively. An iron-based (on the M-site) bulk MAX phase does not exist. Therefore, other strategies to induce long-range magnetic ordering in bulk MAX phases are necessary to open the path to new functional materials. Here, we demonstrate the nonconventional synthesis of a hith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Furthermore, it should be noted that the temperature dependence of the magnetization appears to be tailored by increasing the amount of nitrogen in the materials. While the magnetization of the parent carbide phase V 2 GeC almost stays constant for temperatures above T > 200 K, representing the MAX phase-typical Pauli paramagnetic behavior, 9,35 the carbonitride and even stronger the pure nitride exhibit a noticeable decrease in the magnetization in the same temperature range upon heating. For temperatures below ∼40 K, the small increase in the susceptibility is a common feature in MAX phase compounds in general 57 and may be attributed to small paramagnetic impurities.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, it should be noted that the temperature dependence of the magnetization appears to be tailored by increasing the amount of nitrogen in the materials. While the magnetization of the parent carbide phase V 2 GeC almost stays constant for temperatures above T > 200 K, representing the MAX phase-typical Pauli paramagnetic behavior, 9,35 the carbonitride and even stronger the pure nitride exhibit a noticeable decrease in the magnetization in the same temperature range upon heating. For temperatures below ∼40 K, the small increase in the susceptibility is a common feature in MAX phase compounds in general 57 and may be attributed to small paramagnetic impurities.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%
“…The isothermal magnetization curves (Figure 4a−c) show distinctively different magnetization behavior for all three MAX phases at 300 and 2 K. At 300 K, all compounds show a strictly linear field-dependent magnetization, typical for paramagnetic MAX phases. 9,29 However, at 2 K, the magnetization is nonlinear with respect to the magnetic field, and the hysteresis loops of V 2 GeC 0.5 N 0.5 and V 2 GeN indicate the presence of a superconducting state. As the dimensionless volume susceptibility is substantially larger than a value of χ = −1 (V 2 GeC 0.5 N 0.5 : χ 2K = −0.010, V 2 GeN: χ 2K = −0.017), the feature in the hysteresis loops does not represent MAX phase bulk superconductivity but most likely a superconducting secondary phase, which is not assignable in the XRD data.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[110] Furthermore, the research area still holds a great potential as shown in recent literature reports. [103,106] Besides, the formation of solid solution phases is not only restricted to MAX phases, they have also shown benefits for specific properties of MXenes. [111]…”
Section: Most Common M-elementsmentioning
confidence: 99%
“…[102] Recent studies on phases with three or more elements (e. g. (Ti,Nb,Ta,V) 4 AlC 3 [103] ) push towards "high entropy" [104,105] MAX phases using the common transition metals of groups 4-5 leading to compounds with enhanced mechanical properties. However, "conventional" two element M-site solid solution phases still exhibit large potential as just shown with the synthesis of (V 1-x Cr x ) 2 GaC, [106] a solid solution phase almost matching the Stoner criterion. In general, the synthesis and characterization of M-site solid solution phases consisting of the early transition metals that MAX phases were initially known for, have enabled tailoring specific materials properties such as oxidation resistance, [107,108] mechanical characteristics, [103,109] or thermal properties.…”
Section: Most Common M-elementsmentioning
confidence: 99%
See 1 more Smart Citation